Christian-Islamic dialogue and Orientalism problem - Al-Ajmi, Nora Mohammed (Journal of Islamic Sciences, 2023)
This study aims to identify the historical development of Christian-Islamic dialogue and Orientalism problem and its relationship to Christianity and proselytizing, as well as to identify the relationship between Orientalism and the call for Christian-Islamic dialogue. And predicting the phenomenon or idea under study, which helps to generalize about this phenomenon, as well as the comparative approach; To identify the political, religious and social ideas of both the Islamic and Christian sides in the dialogue, and to show the similarities and differences as much as possible in each pivotal idea dealt with by the Islamic and Christian sides. The study consists of four topics; The first topic dealt with "the historical development of the phenomenon of Islamic-Christian dialogue" from two demands in which the researcher discussed the estrangement in dialogue and the emergence of its precursors, and the actual launch of the Islamic-Christian dialogue and its continuity. And his activities and his desire to assimilate Islam and curtail its call. In the third topic, "The Characteristics and Controls of Islamic-Christian Dialogue," the researcher discussed, through two demands, the political characteristics of Christian-Islamic dialogue, and the controls of Christian-Islamic dialogue. They demanded the political motives for the Islamic-Christian dialogue, and the political obstacles to the Islamic-Christian dialogue. The study reached important results, the most prominent of which is that Orientalism is an intellectual current that is heading towards the East to study its civilization, religions, culture, language and literature through ideas that were mostly characterized by fanaticism and the desire to serve colonialism and Christianize Muslims and make them a metamorphosis of Western culture by spreading their inferiority, and the study also concluded that the Christian side is more manageable This is due to the fact that the Christian side, which made the Christian side determine the topics that will be discussed, and the study recommended the organic unity of Muslims; Because it is the only protection for them against any colonial, imperial, or Orientalist attacks, and that Orientalism would not have emerged and developed had it not been for the inability of Muslims themselves to reach the Western mind and try to shape it according to the correct Islamic epistemological pattern, or at the worst, to neutralize its position towards Islam.